Demystifying Eukaryote Lateral Gene Transfer (Response to Martin 2017 DOI: 10.1002/bies.201700115). (15th March 2018) - Leger, Michelle M.; Eme, Laura; Stairs, Courtney W.; Roger, Andrew J.
Abstract : In a recent BioEssays paper [W. F. Martin, BioEssays 2017, 39, 1700115], William Martin sharply criticizes evolutionary interpretations that involve lateral gene transfer (LGT) into eukaryotic genomes. Most published examples of LGTs in eukaryotes, he suggests, are in fact contaminants, ancestral genes that have been lost from other extant lineages, or the result of artefactual phylogenetic inferences. Martin argues that, except for transfers that occurred from endosymbiotic organelles, eukaryote LGT is insignificant. Here, in reviewing this field, we seek to correct some of the misconceptions presented therein with regard to the evidence for LGT in eukaryotes. Abstract : A recent paper dismisses claims of lateral gene transfer (LGT) into eukaryotic genomes. We counter the arguments made in that paper and discuss the extensive evidence for LGT in eukaryotes.